2013
DOI: 10.4028/www.scientific.net/kem.544.276
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Mechanical Properties of a Novel Biomedical Magnesium-Based Scaffold

Abstract: Magnesium has been recently recognized as a biodegradable metal for bone substitute applications. In the present work, a novel magnesium based scaffold with a specific two-layer structure was prepared for powder metallurgical process. The outer layer of the scaffold shows an interconnected porous structure, so that the fresh fluid can be easily sent into the material, allowing the ingrowth of new bone tissue. The inner compact structure reinforced by the salt particles can increase the strength of the material… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…Their porosity is highly tunable, affecting the stiffness and strength of the scaffold, the diffusion capacity, and the extent of the migration of the cells, playing with the density of the tissue generated [ 123 , 124 ]. Biodegradable porous metallic scaffolds can be made by selective laser melting [ 125 ], powder metallurgy [ 126 ], injection of inert gas into a melt [ 127 ], sintering of particles [ 128 ], vacuum foaming [ 129 ], investment casting [ 130 ], thixocasting [ 131 ], and other methods [ 122 ].…”
Section: Three-dimensional Cell Culture Methodsmentioning
confidence: 99%
“…Their porosity is highly tunable, affecting the stiffness and strength of the scaffold, the diffusion capacity, and the extent of the migration of the cells, playing with the density of the tissue generated [ 123 , 124 ]. Biodegradable porous metallic scaffolds can be made by selective laser melting [ 125 ], powder metallurgy [ 126 ], injection of inert gas into a melt [ 127 ], sintering of particles [ 128 ], vacuum foaming [ 129 ], investment casting [ 130 ], thixocasting [ 131 ], and other methods [ 122 ].…”
Section: Three-dimensional Cell Culture Methodsmentioning
confidence: 99%
“…44 In general, the Young's modulus and maximum stress of porous Mg under compression increases with reduction of porosity and pore size. From the tabulated data (Table 1), the authors concluded that the compressive Wen et al [43][44][45] Pure Mg PM (Carbamide) 30-35 Yamada et al 46 AZ91 Infiltration casting -Zhuang et al 47 Pure Mg PM (Carbamide) 7, 38, 55 Fang et al 48 Pure Mg Laser perforation technique 42.6-51 Witte et al 49,50 AZ91D PM (Salt) 72-76 Gu et al 51 Pure Mg GASAR a 28 AE 1.3 Nguyen et al 52 Pure Mg Infiltration casting 35-80 Kirkland et al 53 Pure Mg Infiltration casting -Zhang et al 54 Pure Mg PM (Salt) -Seyedraoufi and Mirdamadi 55 Mg-Zn PM (Carbamide) 21, 29, 36 Kang et al 56 HA-coated Mg Spark plasma sintering (SPS) 50, 60, 70 Capek and Vojtech 57,58 Pure Mg PM (Carbonate hydrogen ammonium) 29-31 Trinidad et al 59 ZM20, ZMW200, ZXM200, AZ91E, and WE43…”
Section: Manufacturing Processes and Mechanical Propertiesmentioning
confidence: 99%
“…7072 The porosity of porous Mg-based implants has an obvious relationship towards the mechanical properties of the implant. It has been reported from various studies of porous Mg-based materials 44,48,54,7278 that increasing porosity resulted in a depreciation of the mechanical properties. In fact, increasing of pore size of porous Mg-based implants resulted in a decrease of the peak stress.…”
Section: Introductionmentioning
confidence: 99%